HEARTATTACK DETECTION BY HEARTBEAT SENSING USING IOT - NANABOINA VINAY; SURAYA MUBEEN (Utilitas Mathematica, 2025)
Heart disease is a leading cause of mortality worldwide, necessitating the development of early detection systems to prevent fatal incidents. This paper presents an IoT-based heart attack detection system that utilizes a pulse oximeter (SPO2 sensor), vibration sensor, DHT11 temperature and humidity sensor, and GPS module to monitor vital parameters in real time. The system continuously tracks the patient's heart rate, oxygen saturation, body temperature, and physical activity. When critical values indicating a possible heart attack are detected, the system sends emergency alerts to caregivers and medical professionals via an IoT platform, along with real-time GPS location data. This system enhances patient safety by enabling timely medical intervention. Machine learning algorithms are employed to detect abnormal heart rhythms, and users are notified in real-time, ensuring timely intervention and medical assistance. This paper presents the architecture, working mechanism, and potential benefits of the proposed system.